"Sense of Place": Human Wellbeing Considerations for Ecological Restoration in Puget Sound. Issue 5 (2nd September 2016) - Poe, Melissa R.; Donatuto, Jamie; Satterfield, Terre
ABSTRACT: Sense of place is increasingly recognized as key to human wellbeing in social-ecological systems. Yet there is limited understanding about how to define and evaluate it for restoration. Here, we examine the connections between sense of place and human wellbeing for Puget Sound in the context of ecological restoration for shellfish harvesting and other shoreline activities. Using a mixed-methods approach, including semi-structured interviews and participatory workshops with tribal and non-tribal residents, we examined sense of place in two regions of Puget Sound. Empirical results show that people's senses of place are multi-dimensional and derived from: (1) activities in the near-shore; (2) cultural practices and familial heritage; (3) sensory and emotional experiences; and (4) the maintenance and strengthening of social connections. We also found that three conditions play important roles in enabling and fostering place attachment: access, knowledge, and ecological integrity. Improved understanding of a practice-based sense of place is key to creating and enacting successful, resident-supported restoration activities.